Spatial Distribution of Nutrient in The Waters of Haruku Strait, Central Maluku Regency, Maluku Province - Simon Tubalawony; Elvira D Sopalauw; Frederika S Pello (Grouper, 2024)
Strait waters are influenced by tides, water masses and surrounding land. This study aims to analyze the spatial distribution of nutrients in the waters of the Haruku Strait, Central Maluku Regency, Maluku Province. The research method used is the survey method by taking water samples. Water samples were taken from 17 observation stations spread across the Haruku Strait at depths of 1 meter, 25 meters and 50 meters using the Niskin Bottle Water Sampler. Nitrate concentration analysis using the OPTIZEN Alfa equipment (Spectrophotometer UV-Vis) and the Brucine Sulfate method (SNI: 06-2480-1991) and phosphate concentration analysis using the Ammonium Molybdate method (APHA 10th ed. 5400-PD, 1998). The time of observation took place on July 23, 2022. The results showed that the average concentration of nitrate at a depth of 1 m was 1.146 ± 0.647 mg/L, a depth of 25 m was 1.148 ± 0.709 mg/L and a depth of 50 m was 1.136 ± 0.701 mg/L while the average concentration of phosphate at a depth of 1m was 0.051 ± 0.028 mg/L, a depth of 25 m was 0.053 ± 0.029 mg/L and at a depth of 50 m was 0.049 ± 0.020 mg/L. The waters of the Banda Sea, the Seram Strait and contributions from the rivers on the coast of Ambon Island play a role in the distribution of nutrients in the waters of the Haruku Strait.